2014
DOI: 10.5603/ep.2014.0030
|View full text |Cite
|
Sign up to set email alerts
|

Zmiana stężenia CGRP w osoczu u pacjentów z dysfunkcją układu ruchowego narządu żucia leczonych szynami okluzyjnymi — badanie randomizowane

Abstract: Introduction: Occlusal splint therapy is a well-known method for the treatment of TMD. Muscle stretching and pain relief are effects of occlusal appliance. The aim of this study was to evaluate the plasma level of CGRP in patients with myofascial pain (RDC/TMD Ia) and myofascial pain with limited opening (RDC/TMD Ib) before and after muscle stretching with occlusal splint therapy. Material and methods: A randomised trial was performed including 35 subjects (males = 10, females = 25) in the experimental group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Three studies included minimal treatment (exercise and counseling) [ 21 , 46 , 56 ], and one study used counseling as control group [ 45 ]. Seven studies had no treatment as control group [ 44 , 50 , 51 , 54 , 57 59 ]. Six studies had two control groups [ 44 46 , 50 , 51 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included minimal treatment (exercise and counseling) [ 21 , 46 , 56 ], and one study used counseling as control group [ 45 ]. Seven studies had no treatment as control group [ 44 , 50 , 51 , 54 , 57 59 ]. Six studies had two control groups [ 44 46 , 50 , 51 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…These include the stabilization splint, soft splint, flat splint, and pivot splint [11]. Although the mechanisms of action of splints are not fully understood, Aleksandra et al [28] found that plasma levels of calcitonin gene related peptide (CGRP) were increased in TMD patients treated with an occlusal splint. CGRP is a potent neuropeptide thought to play an essential role in stretching and relaxing muscle, neurogenic vasodilatation and maintaining the functional integrity of peripheral tissues [29].…”
Section: Discussionmentioning
confidence: 99%